Understanding the drivers of remittances to Pakistan - David de Padua; Matteo Lanzafame; Irfan A. Qureshi; Kiyoshi Taniguchi (Asian Development Bank (ADB), 2024)
Remittances are an important source of external financing in Pakistan, amounting to around 10% of gross domestic product in 2021. As such, an appropriate understanding of the key macroeconomic drivers of remittances has important policy implications. Combining a database of bilateral remittances between Pakistan and its main remittance-sending countries with monthly macroeconomic data over 2003-2021, we use a Bayesian vector autoregression model to understand the drivers of remittances to Pakistan. Specifically, we do so by estimating the impact of various structural shocks on remittance growth in Pakistan. We find that macroeconomic variables, including economic activity, inflation, equity markets, and interest rates-both in Pakistan and migrants' host countries-play a significant role, and their contributions vary over time.
Keywords: E7; F22; F24; 330; remittances; macroeconomics; Pakistan